PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING PADA MATERI ARITMATIKA SOSIAL - Hidayati Rais; Awatif Awatif; Ramadhani Ramadhani; Ifrianto Ifrianto (STKIP Pesisir Selatan, 2022)
This research aims to develop LKPD based on problem based learning on social arithmetic subject matter for class VII students of SMP Negeri 5 Merangin which is valid, practical, and effective. This form of research is known as Research and Development (R&D) and uses the ADDIE development model which has five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The instrument used was a validation sheet filled out by five validators, a practicality questionnaire sheet and an interview guide for student responses and effectiveness in the form of observation sheets and learning outcomes test questions. These results show that the average score of the material expert validation is 4.27, the linguist validation is 4.40, and the media expert validation is 4.68. The overall validation value of 4.45 has a very valid category. The results of the student response questionnaire obtained a percentage of 80.32% having a fairly practical category. Student learning activities get an average percentage of 76.57% having an active category and the percentage of classical learning outcomes of 76.92% having an effective category. Thus, this research resulted in PBL-based LKPD for social arithmetic subject matter for grade VII students of SMPN 5 Merangin which was valid, practical, and effective